Fierro, M. A. (2022). Platón. Fedro. Traducción, notas, introducción y comentarios. Ciudad Autónoma de Buenos Aires, Colihue (335 páginas) - Merico, Valentina (2023)
Reseña del libro Platón. Fedro. Traducción, notas, introducción y comentarios por M. A. Fierro